Motives for Choosing the Profession of a Social Care Teacher in the Universities of Kazakhstan - Shaumen, Guldana Sarsenbaykyzy; Meterbayeva, Kulbarshyn Meterbayevna; Baitasov, Azamat Ametbekovich; Utyupova, Gulnar Eletaevna (International Review of Management and Marketing, 2016)
This research is aimed at identifying the motives for choosing the profession of a social care teacher by university students in Kazakhstan, their level of preparedness for this profession. The comparative study involved 106 students, 70 of which are first-year students and 36 are fourth-year students of the Kazakh National University named after Al-Farabi and Pavlodar State Pedagogical Institute with the specialization 5B012300 "Social pedagogy and self-knowledge". During the research such methods as questionnaires and statistical data processing were used. The comparative analysis of the main types of motivation in choosing the profession of a social care teacher by students allowed us to reveal the leading motives, determine the dynamics of determining motives. The results of the survey on the basis of statistical data allowed determining the attitude of students to the profession of a social care teacher, their professional plans, views on education and professional identity. Professional self-determination of students of the social care teacher profession has a multi-directional motivation structure. The research has shown that internal motives mainly influenced the students’ choice of the profession of a social care teacher. Internal motives are complemented by the influence of external motivation of both positive and negative connotations. Fourth-year students have slightly decreased motives indicators such as "Opportunity for creativity", "Opportunities of professional skills growth", "Opportunity of intellectual and physical development". Evaluating the social care teacher’s qualities highly, students often doubt if they have these qualities themselves. More than a half of the students devote themselves to the profession of a social care teacher, 50% of which believe that in the country the problem with street children and adolescents is very relevant and they plan to work mainly with teenagers and children in the future. Keywords: motive, motivational sphere, motivation of choosing a profession, professional self-determination, professional plans JEL Classifications: I20; I21; I23